Accounting for phylogenetic relatedness in cross-species analyses of telomere shortening rates. (5th May 2020) - Radersma, Reinder; Pepke, Michael Le; Eisenberg, Dan T.A.
Abstract: Telomeres are repeating DNA sequences found on the ends of chromosomes, which shorten with age and are implicated in senescence. Cross-species analyses of telomere shortening rates (TSR) and telomere lengths are important for understanding mechanisms underlying senescence, lifespan and life-history strategies of different species. Whittemore et al. (2019) generated a new dataset on variation in TSR, lifespan and body mass. In phylogenetically uncorrected analyses they found that TSR negatively correlates with lifespan. We re-ran analyses of their dataset using appropriate phylogenetic corrections. We found a strong phylogenetic signal in the association between TSR and body mass. We were able to corroborate Whittemore et al.'s major findings, including while correcting for body mass in a multivariate analysis. Since laboratory mice have different telomere lengths and potentially different telomere dynamics than wild mice, we removed mice from the analysis, which attenuates most associations.